2023
DOI: 10.1371/journal.pone.0280197
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning (ACP) to promote receipt of value-concordant care: Results vary according to patient priorities

Abstract: Background Benefits of advance care planning (ACP) have recently been questioned by experts, but ACP is comprised of discrete activities. Little is known about which, if any, ACP activities are associated with patients’ greater likelihood of receiving value-concordant end-of-life (EoL) care. Objectives To determine which ACP activities [Do-Not-Resuscitate (DNR) order completion, designation of a healthcare proxy (HCP), and/or EoL discussions with physicians], individually and in combination, are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…In this regard, the results of a systematic review show that the EOL priority was fixed for more than 70% of patients [ 86 ]. Among patients with advanced cancer who prioritized comfort-focused care at the EOL, engaging in an EOL discussion with their physician and completing DNR orders were both significantly related with receiving valuable EOL care [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the results of a systematic review show that the EOL priority was fixed for more than 70% of patients [ 86 ]. Among patients with advanced cancer who prioritized comfort-focused care at the EOL, engaging in an EOL discussion with their physician and completing DNR orders were both significantly related with receiving valuable EOL care [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, prior research has indicated that patients with ADs who specifically requested comfort care were more likely to receive treatments aligned with their wishes compared to those without such directives. 27…”
Section: Discussionmentioning
confidence: 99%
“…However, prior research has indicated that patients with ADs who specifically requested comfort care were more likely to receive treatments aligned with their wishes compared to those without such directives. 27 These limitations highlight the need for further research to explore a broader range of AD sources and evaluate the actual impact of pain relief provisions and how they directly affect patients, families, and the healthcare team. While earlier studies offer valuable context by emphasizing the significance of ADs in aligning treatments with patients' wishes, they do not directly examine the effectiveness of pain relief provisions.…”
Section: Implications and Limitations Of The Studymentioning
confidence: 99%
“…Thirty-eight studies [15–52] and three reviews were identified [6 ▪ ,8 ▪▪ ,13 ▪▪ ]. Studies were heterogeneous in terms of cancer care contexts, population size and characteristics, research designs, and assessment methods (Table 1).…”
Section: Literature Search and Samplementioning
confidence: 99%
“…Fourteen articles that were not included in these categories are reported in Table 1. They address two topics: ACP uptake rates [39–44]; and ACP outcomes [45–52].…”
Section: Overview Of Factors Influencing Advance Care Planning Commun...mentioning
confidence: 99%